1998
DOI: 10.1093/ndt/13.3.700
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous peritoneal dialysis catheter insertion and removal in catheter-related infections without interruption of peritoneal dialysis

Abstract: Catheter-related infections result in high patient morbidity, the need for temporary haemodialysis, and high costs. These infections are the main cause of limited technique survival in peritoneal dialysis. We introduced a protocol for the simultaneous peritoneoscopic insertion and removal of peritoneal catheters in patients with catheter-related infections. Peritoneal dialysis was continued the day after surgery using low-volume dwells and a dry abdomen during the daytime. The dialysate leukocyte count had to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 0 publications
1
42
0
1
Order By: Relevance
“…In the scenario of catheter infections, however, a few observational studies showed that simultaneous removal and reinsertion of the dialysis catheter with a new exit site under antibiotic coverage is effective in eradicating the infections (169)(170)(171)174,201,202). However, there is no controlled trial in this area.…”
Section: Catheter Removal and Reinsertionmentioning
confidence: 99%
“…In the scenario of catheter infections, however, a few observational studies showed that simultaneous removal and reinsertion of the dialysis catheter with a new exit site under antibiotic coverage is effective in eradicating the infections (169)(170)(171)174,201,202). However, there is no controlled trial in this area.…”
Section: Catheter Removal and Reinsertionmentioning
confidence: 99%
“…Most clinicians have chosen to insert the new catheter before removing the old catheter, but the alternative approach has been taken with similar results (267,270,282).…”
Section: Guideline 175mentioning
confidence: 99%
“…Although no standard dialysis prescription exists for immediate resumption of PD, a low volume, supine, intermittent PD protocol to minimize the risk of leak was used in most studies (5,7,10,12,13). The use of a cycler in this clinical setting is particularly convenient.…”
Section: Discussionmentioning
confidence: 99%